Effects of stress management program on the quality of nursing care and intensive care unit nurses - Saied Pahlavanzadeh; Zohreh Asgari; Nasrollah Alimohammadi (Wolters Kluwer Medknow Publications, 2016)
Background: High level of stress in intensive care unit nurses affects the quality of their nursing care. Therefore, this study aimed to determine the effects of a stress management program on the quality of nursing care of intensive care unit nurses. Materials and Methods: This study is a randomized clinical trial that was conducted on 65 nurses. The samples were selected by stratified sampling of the nurses working in intensive care units 1, 2, 3 in Al-Zahra Hospital in Isfahan, Iran and were randomly assigned to two groups. The intervention group underwent an intervention, including 10 sessions of stress management that was held twice a week. In the control group, placebo sessions were held simultaneously. Data were gathered by demographic checklist and Quality Patient Care Scale before, immediately after, and 1 month after the intervention in both groups. Then, the data were analyzed by Student's t-test, Mann-Whitney, Chi-square, Fisher's exact test, and analysis of variance (ANOVA) through SPSS software version 18. Results: Mean scores of overall and dimensions of quality of care in the intervention group were significantly higher immediately after and 1 month after the intervention, compared to pre-intervention (P < 0.001). The results showed that the quality of care in the intervention group was significantly higher immediately after and 1 month after the intervention, compared to the control group (P < 0.001). Conclusions: As stress management is an effective method to improve the quality of care, the staffs are recommended to consider it in improvement of the quality of nursing care.